Commentary: Constructing Refugees in the Academic Discourse: The Hmong in America by Marc Dorpema - Marc Dorpema (Hmong Studies Journal, 2019)
Produced in a historiographical spirit, this literature review traces trends in the depiction of Hmong Americansnot in popular representations such as newspapers or public perception, but in the American academic discourse itself. By adopting a thematic approach, it evidences the curious chronological development of which aspects of Hmong studies were treated in which way from the 1980s until the present. To this extent, the paper argues that while the 1980s and 1990s saw a heavy emphasis on social scientific studies of Hmong family ties and clan structure which, while careful and mostly sensitive in their treatment, nevertheless on occasion construct the Hmong as either irreconcilably or undesirably different(sections I and II). It then proceeds to crystallise the significant treatment of education with respect to the Hmong, which, produced in particular in the late 1990s and early 2000s, presented powerful cases of forced assimilation through the lens of Hmong Americans themselves(section III). A brief fourth section focuses on the marginal role ascribed to economic problems encountered by the Hmong, treated as almost inevitable.Crucially, the fifth section proceeds to problematise more recent feminist critiques.The argument presented here is that their central drawback lies in the appropriation and overriding of Hmong voices for a particular project.This construction of Hmong voices, finally, is on the retreat in most recent studies which, centred on horticulture, music, rituals and medicine –to name but a few –attempt to elucidate the Hmong American experience through the lens of the protagonists themselves. This is an important step, and one which must be pursued further.